Pilot scale production of coconut residue cookies - Collantes, Mabelle Valdez; Dumelod, Benelyn Domingo (1995)
Pilot scale production of coconut residue cookies was done to assess the efficiency of upscaling the process and to test the reproducibility of the standardized process and formulation. The coconut residue cookies produced in pilot scale were compared with those from bench scale in terms of microbial load, sensory characteristics, proximate composition and cost. Results showed a microbial load of 9,650 cfu/g which was within limits, indicating efficient processing and product handling. Sensory evaluations done on the samples from bench and pilot scale productions showed no significant differences--the products were light brown, with a distinct coconut taste, and a general acceptability ranking of "liked moderately". The product contained 1.48% moisture, 4.61% protein, 38.51% fat, 21.50% total dietary fiber, 33% total available carbohydrate and 1.4% ash. Each cookie weighs approximately 15 g and costs P0.70. They were packed by 10's; each bag weighing 165 ± 5 g and costing about P7.02.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Cookies; Coconut products